Comparison of Algorithms for the Detection of Enteroviruses in Stool Specimens from Children Diagnosed with Acute Flaccid Paralysis (2017)
This study was designed to compare both the cell culture dependent and independent enterovirus detection algorithms recommended by the WHO and assess how either might impact our perception of the diversity of enterovirus types present in a sample. Sixteen paired samples (16 isolates from RD cell culture and their corresponding stool suspension, i.e., 32 samples) from AFP cases in Nigeria were analyzed in this study. All the samples were subjected to RNA extraction, cDNA synthesis, the WHO recommended RT-snPCR, and its modification. Amplicons were sequenced and strains identified. Enterovirus diversity was the same between the isolates and fecal suspension for the control and five of the samples. It was, however, different for the remaining 10 (62.5%) samples. Nine (CV-B4, E6, E7, E13, E14, E19, E29, EV-B75, and EV-B77) and five (CV-A1, CV-A11, CV-A13, EV-C99, and PV2) EV-B and EV-C types, respectively, were detected. Particularly, E19 and EV-B75 were only recovered from the isolates while E14, EV B77, CV-A11, and CV-A13 were only recovered from fecal suspension. Both the cell culture dependent and independent protocols bias our perception of the diversity of enterovirus types present in a sample. Hence, effort should be directed at harmonizing both for increased sensitivity.